New therapeutic strategies for squamous cell cancer and adenocarcinoma. (11th October 2013) - Wijnhoven, Bas P.L.; Toxopeus, Eelke L.A.; Vallböhmer, Daniel; Knoefel, Wolfram T.; Krasna, Mark J.; Perez, Kimberly; van Rossum, Peter S.N.; Ruurda, Jelle P.; van Hillegersberg, Richard; Schiesser, Marc; Schneider, Paul; Felix, Valter Nilton
Abstract : This paper presents commentaries on neoadjuvant treatment esophagectomy; the prognostic and predictive effects of single nucleotide polymorphisms (SNP) in the multimodality therapy of esophageal cancer; optimal preoperative treatment prior to surgery for esophageal cancer; a possible role for trastuzumab in treating esophageal adenocarcinoma or any esophageal dysplasia/intra‐epithelial neoplasia; surgery after chemoradiation in resectable esophageal cancer; whether para‐aortic lymph node dissection should be performed in esophagogastric junction (EGJ) tumors; and transhiatal esophagectomy in treatment of the esophageal cancer